THE ROLE AND RELEVANCE OF FOREIGN LANGUAGES IN THE EDUCATION SYSTEM OF THE REPUBLIC OF UZBEKISTAN - Fayzullayeva Nodira (Ta’lim innovatsiyasi va integratsiyasi, 2025)
This article highlights the role of foreign languages in the education system of the Republic of Uzbekistan, their strategic importance, the reforms being implemented within the framework of state policy, modern methodological approaches, the international and national certification system, measures aimed at training competitive personnel, and integration processes in international cooperation. Furthermore, it substantiates that in the developing education system of the Republic of Uzbekistan, learning foreign languages is not only a necessity but also a vital foundation for progress.